A Review on Thermal Properties Improvement of Phase Change Materials and Its Combination with Solar Thermal Energy Storage. Issue 7 (27th May 2021) - Liu, Wei; Zhang, Xuelai; Ji, Jun; Wu, Yifan; Liu, Lu
Abstract : This article summarizes measures to enhance the solar phase change thermal energy storage (TES), starting from two key points in solar phase change TES research: solar phase change materials (PCM) and solar phase transition devices. First, different types of PCM and their advantages and disadvantages are introduced. To improve thermal performance, the research progress of different dimensional thermal conductivity additives, photothermal composite phase change materials (CPCM), and phase change microcapsules is reviewed. Then, the characteristics of commonly used solar phase transition TES devices and the research status of solar energy device improvement with fins and multistage phase transition TES are summarized for the past few years. It is hoped to provide methods and ideas for the design and research of solar phase change TES systems, and to increase the overall heat transfer properties through the combination of multiple optimization methods. Finally, the future direction and research focus of solar phase change TES technology are put forward. Abstract : This article summarizes the methods for enhancing the solar thermal energy storage capacity in terms of both phase change materials and thermal energy storage devices, and provides a proper explanation of the principles. Future directions and challenges are presented. A reference is provided for the enhancement of solar phase change thermal energy storage.